A dynamic programming approach for evaluating a portfolio of R&D projects with a budget - Costa, A.; Paixão, J. P. (SOP Transactions on Applied Mathematics, 2014)
The Real Options approach has proved to be a suitable methodology for capturing the flexibility in the investment decision process. This is very useful for the financial evaluation of R&D projects where there are several possible decisions concerning to the investment – delaying, improving or abandoning. Since the risk of an R&D project is usually due to singular characteristics of the project and is uncorrelated with the financial markets, the contingent claims analysis may be not adequate to value R&D projects. Based on a dynamic programming evaluation model, presented in Huchzermeier and Loch [1], we propose an approach to valuing a portfolio of R&D projects with a budget. Specifically, considering a budget constraint, we make an extension of the model mentioned above for assessing the projects in the portfolio simultaneously. To test the proposed evaluation procedure, we generated several R&D portfolios with different dimensions and characteristics. According to our computational experience, the main conclusions are presented.